2017
DOI: 10.1098/rspb.2016.2140
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid enhances cold tolerance in honeybee larvae

Abstract: The natural composition of nutrients present in food is a key factor determining the immune function and stress responses in the honeybee (Apis mellifera). We previously demonstrated that a supplement of abscisic acid (ABA), a natural component of nectar, pollen, and honey, increases honeybee colony survival overwinter. Here we further explored the role of ABA in in vitro-reared larvae exposed to low temperatures. Four-day-old larvae (L4) exposed to 258C for 3 days showed lower survival rates and delayed devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 51 publications
4
35
0
Order By: Relevance
“…In addition, ABA injection appeared to act negatively on 20E signaling by delaying the peak of 20E by 16 h (De Man et al, 1981). ABA from nectar and pollen ingested by honeybees (Apis mellifera) can be detected in honey (Lipp, 1990) and ingestion of ABA by honeybee larvae can increase cold tolerance and cellular immunity (Negri et al, 2017;Ramirez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ABA injection appeared to act negatively on 20E signaling by delaying the peak of 20E by 16 h (De Man et al, 1981). ABA from nectar and pollen ingested by honeybees (Apis mellifera) can be detected in honey (Lipp, 1990) and ingestion of ABA by honeybee larvae can increase cold tolerance and cellular immunity (Negri et al, 2017;Ramirez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Abscisic acid (ABA) is a phytohormone that regulates fundamental physiological functions in plants [ 11 ] and whose presence has been unambiguously demonstrated in nectar and honey [ 12 , 13 , 14 ] as well as in adult honey bees [ 12 , 15 , 16 ]. In the last decade, evidence has been accumulated demonstrating that ABA operates as a cytokine in animal cells by stimulating innate immune defences such as cell migration and phagocytosis and by inducing NO and reactive oxygen species (ROS) production [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“… ABA supplementation enhanced phenoloxidase activity in adult bees [ 15 ]. ABA supplementation enhanced colony survival through winter in field approaches [ 15 ] and recently we have reported that ABA enhances cold tolerance in honeybee larvae [ 16 ]. …”
Section: Introductionmentioning
confidence: 99%
“…This group of authors showed that bees, supplemented with ABA (which increases the catalase activity of worker bees), tolerated almost twice the concentration of some organic pesticides. Besides that, results of Ramirez et al [40] supported a role for ABA increasing the tolerance of honeybee larvae to low temperatures through priming effects. In our study cis, trans-ABA varied from 0.005 (clone XIV/5) to 0.331 lg/ml (clone IX/P).…”
Section: Quantitative Phenolic Profile Of Sour Cherry Nectarmentioning
confidence: 82%